The Effect of The Addition of Chitosan and Calcium Silicate on The Characteristic of Bioplastics from Corn Starch - Ricky Jhon; Haryanto (Universitas Muhammadiyah Purwokerto, 2022)
Plastic waste in Indonesia has an impact that has caused high levels of environmental pollution. The use of plastic in everyday life as a packaging continues to increase, causing plastic waste to increase day by day. Plastic waste derived from petroleum raw materials is difficult to decompose by microbes in the soil. Biodegradable plastics are plastics that can be degraded by microorganisms and are made from renewable materials. Research on the use of biodegradable plastic synthesis has been developed because it is environmentally friendly and renewable. Biodegradable plastic is an alternative material to replace conventional plastic packaging so as not to pollute the environment. Biodegradable plastic is made with natural polymers as the main ingredient so that it is easily digested by microorganisms. Corn starch is a waste from corn processing used by the food industry. The starch content in corn starch can be used to make biodegradable plastic. In this study, biodegradable plastic was synthesized from corn starch with chitosan and calcium silicate as filler and then glycerol as a plasticizer. The purpose of this study was to determine the variation of filler on the results of biodegradable plastics made. The characteristics of biodegradable were marked by the presence of Tensile Strength, Elongation and Biodegradibility tests according to SNI Standards. The highest Tensile Strength value was obtained for the Chitosan variation of 2.62 Mpa and for the Calcium Silicate Variation of 2.8 Mpa, then for the Elongation Value for the Chitosan and Calcium Silicate Variations in accordance with SNI standards, which was 10-40% and for the Biodegradability of Chitosan and Calcium Silicate Variations. Calcium Silicate about 35-40 days.